2018
DOI: 10.3390/toxins10100397
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Triterpenes and a P-I Type Snake Venom Metalloproteinase: Molecular Simulations and Experiments

Abstract: Small molecule inhibitors of snake venom metalloproteinases (SVMPs) could provide a means to rapidly halt the progression of local tissue damage following viperid snake envenomations. In this study, we examine the ability of candidate compounds based on a pentacyclic triterpene skeleton to inhibit SVMPs. We leverage molecular dynamics simulations to estimate the free energies of the candidate compounds for binding to BaP1, a P-I type SVMP, and compare these results with experimental assays of proteolytic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Moreover, molecular simulations performed by Negi et al demonstrated that ursolic acid can snugly fit into the active site of JNK1 [ 92 ]. In the case of matrix metalloproteinases-2/-9, primary effects of triterpenoids on their activity, as far as we know, have not been yet published, however, recently, Preciado et al reported that betulinic, oleanolic and ursolic acids can bind to catalytic site of snake venom metalloproteinases, being similar to those in human matrix metalloproteinases, and significantly inhibit their enzymatic and biological activities [ 93 , 94 ]. Furthermore, CDDO-Me and its analog RTA408 were found to decrease expression of MMP-9 in various models, including tumor necrosis factor α- (TNF-α-), receptor activator of nuclear factor kappa-B ligand- (RANKL-) and interleukin 1β- (IL-1β)-stimulated chronic myelogenous leukemia KBM-5 cells, RAW264.7 macrophages and rat brain astrocytes [ 72 , 95 , 96 ], respectively, as well as primary mammary tumor cells, isolated from polyoma middle T mice [ 97 ], which is consistent with revealed ability of SM to inhibit expression of MMP-9 in metastatic foci in lungs of B16 melanoma-bearing mice ( Figure 8 E).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, molecular simulations performed by Negi et al demonstrated that ursolic acid can snugly fit into the active site of JNK1 [ 92 ]. In the case of matrix metalloproteinases-2/-9, primary effects of triterpenoids on their activity, as far as we know, have not been yet published, however, recently, Preciado et al reported that betulinic, oleanolic and ursolic acids can bind to catalytic site of snake venom metalloproteinases, being similar to those in human matrix metalloproteinases, and significantly inhibit their enzymatic and biological activities [ 93 , 94 ]. Furthermore, CDDO-Me and its analog RTA408 were found to decrease expression of MMP-9 in various models, including tumor necrosis factor α- (TNF-α-), receptor activator of nuclear factor kappa-B ligand- (RANKL-) and interleukin 1β- (IL-1β)-stimulated chronic myelogenous leukemia KBM-5 cells, RAW264.7 macrophages and rat brain astrocytes [ 72 , 95 , 96 ], respectively, as well as primary mammary tumor cells, isolated from polyoma middle T mice [ 97 ], which is consistent with revealed ability of SM to inhibit expression of MMP-9 in metastatic foci in lungs of B16 melanoma-bearing mice ( Figure 8 E).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the authors suggested that glycolic acid chelated the cofactor Zn 2+ employing fluorescence studies, chelation assays, and molecular docking. Other natural products tested against the same SVMP were triterpenic acids (65,66), which inhibited the enzymatic activity of the enzyme, and they were characterized as competitive inhibitors. Moreover, these compounds inhibited the hemorrhagic, myotoxic, and edema-forming activities provoked by this toxin.…”
Section: Until Todaymentioning
confidence: 99%